Vibrio parahaemolyticus: a review on the pathogenesis, prevalence, and advance molecular identification techniques - Letchumanan, Vengadesh; Chan, Kok-Gan; Lee, Learn-Han (Frontiers in Microbiology, 2014)
Vibrio parahaemolyticus is a Gram-negative halophilic bacterium that is found in estuarine, marine and coastal environments. Vibrio parahaemolyticus is the leading causal agent of human acute gastroenteritis following the consumption of raw, undercooked or mishandled marine products. In rare cases, Vibrio parahaemolyticus causes wound infection, ear infection or septicaemia in individuals with pre-existing medical conditions. Vibrio parahaemolyticus has two hemolysins virulence factors that are thermostable direct hemolysin (tdh)-a pore-forming protein that contributes to the invasiveness of the bacterium in humans, and TDH-related hemolysin (trh), which plays a similar role as thermostable direct hemolysin (tdh) in the disease pathogenesis. In addition, the bacterium is also encodes for adhesions and type III secretion systems (T3SS1 and T3SS2) to ensure its survival in the environment. This review aims at discussing the Vibrio parahemolyticus growth and characteristics, pathogenesis, prevalence and advances in molecular identification techniques.